Juridical Review Of The Accountability Of The Port Authority and The Port Authority Office (KSOP) In The Evaluation System For The Implementation Of Guidance At The Port: Research Study On Batam Special KSOP - Gahara Herawati; Erniyanti Erniyanti; Soerya Respationo; Bachtiar Simatupang; Darwis Anatami (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
This research is motivated by the importance of the role of KSOP in ensuring that ship guidance at the port is carried out in accordance with the set safety standards, as well as various obstacles that hinder the optimization of the implementation of these responsibilities. These obstacles include limited human resources, budgets, infrastructure, and ineffective coordination and communication. Research Objectives The purpose of this study is to analyze and evaluate the accountability of KSOP in the implementation of guidance at Batam City Port, identify the obstacles faced, and formulate efforts that can be made to overcome these obstacles. Research Methods This research uses normative juridical and empirical sociological methods. The normative juridical method is carried out through a literature study of the laws and regulations that regulate ship guidance and the responsibilities of KSOP. Meanwhile, empirical sociological methods are carried out through observation, interviews, and direct data collection from the Batam Special KSOP and other related parties. Research Results The results of the study show that the implementation of KSOP accountability in the implementation of guidance at the Port of Batam City has not run optimally. Obstacles faced include limited human resources, inadequate budgets, outdated infrastructure and technology, and lack of coordination and communication. In addition, awareness and compliance with safety procedures still need to be increased. Suggestions This study suggests increasing the recruitment and training of ship guides, optimizing budgets, modernizing navigation equipment and communication technology, simplifying regulations, and improving coordination and communication between related parties. With these steps, KSOP is expected to be more effective in supervising and ensuring the implementation of safe and efficient guidance at the Port of Batam City.